PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PASIEN DI PUSKESMAS PLERET BANTUL - Widiyaningsih, Dwi; Raharusun, Halimah (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
Service quality has a close relationship with customer satisfaction. Thus, health centers are expected to maintain patient satisfaction by further maximizing and optimizing service quality so as to reduce the emergence of patient trust problems. Because, satisfaction is an important factor in knowing how patients are loyal to the health center or not. This study is a quantitative descriptive study using a cross sectional design. The location of this research was at the Pleret Health Center. The population in this study was 9,073. Sampling was done by accidental sampling method. The sample size was determined by the slovin formula and got a total sample of 99 respondents. Data were collected using questionnaires and analyzed using univariate, bivariate and multivariate analysis. The results of this study indicate that the percentage contribution of the influence of the independent variables, namely Service Quality and Customer Satisfaction on the dependent variable, is 59.8%. Furthermore, based on simultaneous hypothesis testing (F test), the results obtained are simultaneously the variables of Service Quality and Customer Satisfaction on Patient Loyalty at the Pleret Health Center with the results ð‘“â„Žð‘–ð‘¡ð‘¢ð‘›ð‘” > ð‘“ð‘¡ð‘Žð‘ð‘’ð‘™ 53.984 > 3.940. Partially (t test) Service Quality has a positive and significant effect with a significance result of 0.043 <0.05, Customer Satisfaction has a positive and significant effect with a significance result of 0.000 <0.05.